Phytoplankton Species Diversity in The Manado Bay River's Mouths - Indradewa, I Gede Bagus; Mantiri, Rose O.S.E; Tamanampo, Jan F.W.S. (Sam Ratulangi University, 2018)
The research was conducted in four rivermouths surrounding city of Manado. The first location is Bahu rivermouth, second location is Sario rivermouth, third location is Jengki rivermouth and the fourth location is Bailang rivermouth. Objectives of this study were to reveal the composition of phytoplankton and its ecological indices in those four rivermouths.Method used was considered as descriptive and explorative study. Plankton net with 60 µm mesh size used for samples collection. The volume of water on the cod end was 50 ml which then brought into the laboratory for further identification and density calculation.Fourtyfive in total of phytoplankton species identified on those four rivermouths comprise of 23 marine species and 22 freshwater species. The highest density value (5.99 individu/l) was found in Jengki rivermouth while the lowest found in Bahu rivermouth (0.65 individu/l). Those four rivermouths have diversity index ranging from 0.94 to 2.03 that considered high. This index value shows that there is no dominant species recorded in the study areasKeyword: Phytoplankton, Rivermounth, Manado bay AbstrakPenelitian ini dilaksanakan di empat muara sungai yang terdapat pada Kota Manado. Lokasi pertama di muara sungai Bahu, lokasi kedua di muara sungai Sario, lokasi ketiga di muara Sungai Jengki dan lokasi keempat di muara sungai Bailang. Tujuan penelitian yaitu mengetahui jenis-jenis fitoplankton di keempat muara sungai di Kota Manado kawasan Teluk Manado dan mengetahui kepadatan spesies dan indeks ekologis fitoplankton di keempat muara sungai tersebut. Penelitian ini menggunakan metode deskriptif dan eksploratif. Sampling plankton menggunakan plankton net ukuran 60 µm. Air yang tersaring dan tertampung di cod end sebanyak 50 ml kemudian diidentifikasi dan dihitung kepadatannya.Diperoleh 45 spesies fitoplankton di empat muara tersebut terbagi atas 23 spesies air laut dan 22 spesies air tawar, dengan kepadatan tertinggi sebesar 5,99 ind/l yang terdapat pada muara Jengki dan kepadatan terendah sebesar 0,65 ind/l terdapat pada muara Bahu. Keempat muara tersebut memiliki indeks keanekaragaman 0,94-2,03 yang berarti memiliki tingkat keanekaragaman yang tinggi. Angka ini juga menunjukan bahwa pada daerah ini tidak ada spesies yang terlalu mendominansi suatu wilayah.Kata kunci: Fitoplankton, Muara sungai, Teluk Manado